Inactivation of Polykaryocytogenic and Hemolytic Activities of Sendai Virus by Phospholipase B (Lysolecithinase) - Barbanti-Brodano, G. (1971)
Evidence is presented that lysolecithin is involved in the fusing and hemolytic activities of Sendai virus. Treatment of the virus with phospholipase B (lysolecithinase) specifically inactivates the hemolytic and fusing abilities, without affecting the infectivity and the capability of the virus to hemagglutinate and adsorb to cells. The possible identity of lysolecithin with the “cell fusion factor” of paramyxoviruses and the mechanism of cell fusion are discussed.